Medicinal plants of South Asia : novel sources for drug discovery - Hanif, Muhammad Asif (Elsevier, 2020)
Medicinal Plants of South Asia: Novel Sources for Drug Discovery provides a comprehensive review of medicinal plants of this region, highlighting chemical components of high potential and applying the latest technology to reveal the underlying chemistry and active components of traditionally used medicinal plants. Drawing on the vast experience of its expert editors and authors, the book provides a contemporary guide source on these novel chemical structures, thus making it a useful resource for medicinal chemists, phytochemists, pharmaceutical scientists and everyone involved in the use, sales, discovery and development of drugs from natural sources.